2001
DOI: 10.1073/pnas.261568398
|View full text |Cite
|
Sign up to set email alerts
|

Short-cycle structured intermittent treatment of chronic HIV infection with highly active antiretroviral therapy: Effects on virologic, immunologic, and toxicity parameters

Abstract: Although continuous highly active antiretroviral therapy (HAART)is effective for many HIV-infected patients, it can be toxic and prohibitive in cost. By decreasing the total amount of time patients receive medications, intermittent HAART could reduce toxicity and cost. Therefore, we initiated a pilot study in which 10 HIV-infected individuals receiving effective therapy that resulted in levels of HIV RNA <50 copies per ml of plasma and CD4 ؉ T cell counts >300 cells per mm 3 of whole blood received repeated cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
2
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(100 citation statements)
references
References 38 publications
4
92
2
1
Order By: Relevance
“…Therapeutic vaccines may be most likely to produce virologic remission in patients with the lowest levels of residual replication (3). Likewise, structured intermittent therapy may be most successful in patients with maximal suppression prior to therapy interruption (17). Finally, the ability to predict levels of residual replication may permit assessments of antiviral potency required to sustain virologic suppression and minimize drug toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic vaccines may be most likely to produce virologic remission in patients with the lowest levels of residual replication (3). Likewise, structured intermittent therapy may be most successful in patients with maximal suppression prior to therapy interruption (17). Finally, the ability to predict levels of residual replication may permit assessments of antiviral potency required to sustain virologic suppression and minimize drug toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the understanding of the replication cycle have revealed which events can be selectively inhibited. Although HAART has made significant progress with the development of several promising agents (Debul et al, 2001), additional agents with distinct mechanisms of action are still needed for effective anti-HIV-1 therapy. Furthermore, the importance of being able to treat chronic infection is anticipated from the pathology of HIV-1 infection in vivo (Koup, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Signal induced by a single virion is not improbable, since Irvine et al (34) found that a single peptide ligand could activate TCR signaling in T cells and Baylor et al (11) showed that retinal cells of the eye could detect single photons, indicating a maximum sensitivity for these signal transduction systems to minimal respective stimuli. The probability that two or three virions bind a CD4 ϩ T-cell in vivo is very likely based on the range of plasma HIV RNA copies and CD4 ϩ T-cell counts in chronically infected patients (21,46,68). Importantly, this signaling takes place in the absence of infection, since resting CD4 ϩ T cells are refractory to infection.…”
Section: Cxcr4mentioning
confidence: 99%